Superparamagnetic iron oxide-encapsulating polymersome nanocarriers for biofilm eradication. (March 2017) - Geilich, Benjamin M.; Gelfat, Ilia; Sridhar, Srinivas; van de Ven, Anne L.; Webster, Thomas J.
Abstract: The rising prevalence and severity of antibiotic-resistant biofilm infections poses an alarming threat to public health worldwide. Here, biocompatible multi-compartment nanocarriers were synthesized to contain both hydrophobic superparamagnetic iron oxide nanoparticles (SPIONs) and the hydrophilic antibiotic methicillin for the treatment of medical device-associated infections. SPION co-encapsulation was found to confer unique properties, enhancing both nanocarrier relaxivity and magneticity compared to individual SPIONs. These iron oxide-encapsulating polymersomes (IOPs) penetrated 20 μm thick Staphylococcus epidermidis biofilms with high efficiency following the application of an external magnetic field. Three-dimensional laser scanning confocal microscopy revealed differential bacteria death as a function of drug and SPION loading. Complete eradication of all bacteria throughout the biofilm thickness was achieved using an optimized IOP formulation containing 40 μg/mL SPION and 20 μg/mL of methicillin. Importantly, this formulation was selectively toxic towards methicillin-resistant biofilm cells but not towards mammalian cells. These novel iron oxide-encapsulating polymersomes demonstrate that it is possible to overcome antibiotic-resistant biofilms by controlling the positioning of nanocarriers containing two or more therapeutics. Graphical abstract: